The Impact Of Using Digital Library Resources On The Productivity Of Researchers At The State Islamic Institute Of Purwokerto - Aris Nurohman (Pustakaloka, 2022)
Abstract: Digital library resources are invaluable in assisting universities in research. The academic community recognizes that digital resources improve their research results. Much research has also confirmed the link between the utilization of digital resources and research output. The researchers analyzed the utilization of digital library resources by researchers at the Purwokerto State Islamic Institute to validate the evidence. The study takes a descriptive-analytical approach, employing the purposive sampling method to collect data from various circles of researchers at various levels. The conclusion is that digital information sources are valuable sources of information that should be evaluated and exploited in the research process, beginning with creating ideas, study design, reference sources, and data collection. Researchers have benefited from digital resources due to the ease and speed of access to information, support for improving research performance, improving the quality of scientific work, supporting creativity to continue working, and increasing awareness about the importance of publication and authentication of scientific papers.Keywords: digital library resources, library, researchers, research productivity. Abstrak: Sumber daya perpustakaan digital sangat berharga dalam membantu perguruan tinggi dalam penelitian. Civitas akademika menyadari bahwa sumber daya digital mempengaruhi peningkatan hasil penelitian mereka. Beberapa penelitian juga telah mengkonfirmasi hubungan antara pemanfaatan sumber daya digital dan hasil penelitian. Para peneliti menganalisis pemanfaatan sumber daya perpustakaan digital oleh para peneliti di Institut Agama Islam Negeri Purwokerto untuk memvalidasi bukti. Penelitian ini menggunakan pendekatan deskriptif-analitis, dengan menggunakan metode purposive sampling untuk mengumpulkan data dari berbagai kalangan peneliti di berbagai tingkatan. Kesimpulannya, sumber informasi digital adalah sumber informasi berharga yang harus dievaluasi dan dimanfaatkan dalam proses penelitian, dimulai dengan penciptaan ide, desain studi, sumber referensi, dan pengumpulan data. Para peneliti telah mendapatkan manfaat dari sumber daya digital karena kemudahan dan kecepatan akses informasi, dukungan untuk meningkatkan kinerja penelitian, peningkatan kualitas karya ilmiah, mendukung kreativitas untuk terus berkarya, dan meningkatkan kesadaran akan pentingnya publikasi dan otentikasi karya ilmiah.Kata kunci: sumber daya perpustakaan digital, perpustakaan, peneliti, produktivitas penelitian